2018
DOI: 10.1371/journal.pone.0196873
|View full text |Cite
|
Sign up to set email alerts
|

A return to the genetic heritage of durum wheat to cope with drought heightened by climate change

Abstract: The objective of this work was to perform a comparative analysis of the physiological, biochemical and agronomical parameters of recent and heritage durum wheat cultivars (Triticum durum Desf.) under water-deficit conditions. Five cultivars were grown under irrigated (control) and rainfall (stressed) conditions. Different agro-physiological and biochemical parameters were studied: electrolyte leakage, relative water content, chlorophyll fluorescence, proline, soluble sugars, specific peroxidase activity, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The plant growth regulator, γ-aminobutyric acid, as well as free amino acids and sugars also play a role in scavenging ROS [15]. Other studies have shown an increase in the activity of scavenging enzymes, such as the enhancement of peroxidase activity under water deficit in durum wheat [106]. The plant response to water stress involves a complex of genes and processes regulated by interlinked genetic and biochemical mechanisms [87].…”
Section: Water Stressmentioning
confidence: 99%
“…The plant growth regulator, γ-aminobutyric acid, as well as free amino acids and sugars also play a role in scavenging ROS [15]. Other studies have shown an increase in the activity of scavenging enzymes, such as the enhancement of peroxidase activity under water deficit in durum wheat [106]. The plant response to water stress involves a complex of genes and processes regulated by interlinked genetic and biochemical mechanisms [87].…”
Section: Water Stressmentioning
confidence: 99%
“…This high diversity led to consider North Africa as a secondary diversity center for durum wheat. Slama et al (2018) commented that durum wheat spread from the Fertile Crescent to the Mediterranean basin, reaching the Iberian Peninsula and North Africa about 7000 years before date. Actually cropped on 1.5 million hectares yearly with a variable production, ranging from 0.42 (1986/87) to 3.2 million tons (2016/17), during the 1975-2017 period, durum wheat remains a major cereal crop in Algeria (https://.…”
mentioning
confidence: 99%
“…Indeed, landraces show variation in their response to diverse stress-prone environments, and this heritage may be used as a genetic resource for breeding future crops [16]. For example, sweet potato heirlooms exhibit moderate to high host-plant resistance to soilborne insects, which provides interesting sources for developing new cultivars [17]; Hopi farmers in Arizona in the United States still plant 'Hopi blue maize' because it is adapted to drought and the short growing season and because of cultural significance [18]; native black and yellow maize landraces from Los Tuxtlas, Mexico are efficient phosphorus (P) colonizers and thus adapted to low soil P conditions [19]; farmers from northeast India still cultivate and maintain traditional rice cultivars because of their adaptation to harsh growing conditions [20][21][22]; heritage durum wheat cultivars are more tolerant to drought than modern cultivars [23]; and Spanish and Italian farmers in some regions still cultivate tomato landraces that are highly adapted to drought and salinity [24,25].…”
Section: Heirlooms and Sustainable Agriculturementioning
confidence: 99%